Descriptions of the last instar larvae of Anotogaster chaoi Zhou, 1998 and Neallogaster annandalei (Fraser, 1923) from Erhai Lake Basin, Yunnan, China (Odonata: Cordulegastrids) - Yang, Guo-Hui; Zi, Dong-Dong (Zootaxa, 2023)
The exuviae of Anotogaster chaoi Zhou, 1998 and Neallogaster annandalei (Fraser, 1923) are described and illustrated for the first time from Erhai Lake Basin, Yunnan Province, China, based on the final stage larvae reared in a laboratory. Diagnostic differences between the larvae of congeneric A. chaoi, A. gregoryi Fraser, 1923, as well as N. annandalei and N. hermionae (Fraser, 1927) are discussed, and notes on their habitats are provided.